Case Report: Clinical response to anaplastic lymphoma kinase inhibitor-based targeted therapy in uterine inflammatory myofibroblastic tumor harboring ALK-IGFBP5 fusion - Zhao, Ting; Zhang, Xiaowei; Liu, Xin; Ren, Min; Cheng, Yufan; Wang, Jian; Luo, Zhiguo (Frontiers in Oncology, 2023)
Background An inflammatory myofibroblastic tumor (IMT) is a mesenchymal tumor with a prevalence ranging from 0.04% to 0.7% worldwide, in which the lung is the most common predilection site, accounting for 33% of cases, followed by the abdomen, pelvis, mesentery, and uterus. Approximately 50% of uterine IMTs present as anaplastic lymphoma kinase (ALK) positive along with ALK gene fusion, which lays a solid foundation for the development of ALK-based target therapy to optimize treatment strategies. Case presentation Herein we describe a 57-year-old woman who presented with a slow-growing mass in the uterus for over 10 years and then received surgical resection because of significant progressive enlargement of the mass during follow-up. She was diagnosed with uterine leiomyosarcoma (LMS) with no further interventions until recurrence. We revised the diagnosis to uterine IMT based on diffuse ALK expression, ALK-IGFBP5 gene fusion, and the morphologic features of the tumors by pathology consultation. Based on these, we recommended an ALK tyrosine kinase inhibitor (TKI) treatment, crizotinib (250 mg bid), and she achieved a complete response (CR) with at least 18 months of progression-free survival (PFS). We monitored the dynamics of target lesions and peripheral blood cells at regular intervals through CT scans and routine blood tests during the treatment process. We present patient responses to ALK inhibitor-based targeted therapy with uterine IMT harboring ALK-IGFBP5 fusion, and the neutrophil-to-lymphocyte ratio (NLR) may be an effective indicator to predict prognosis.